The collaborative exploration of alternative futures: A different approach to Theories of Change (CEDIL programme, 2022)
ParEvo is a web application that enables the collaborative construction and exploration of a range of alternative futures: likely and unlikely, desirable and undesirable. These are described in the form of a branching narrative structure, developed over a series of iterations involving the interactions of a group of participants. These detailed storylines about the future contrast with optimistic, skeletal and largely singular views of the future found in diagrammatic ToCs often encountered by evaluators. This webinar will describe a recent ParEvo exercise implemented by the Centre for the Study of Existential Risk (CSER) in Cambridge. In this exercise 11 international experts explored ideas about how global risks associated with biotechnology research could be managed, and mismanaged, in the coming four years. Including how these alternative futures were evaluated by participants and the CSER facilitators. Issues to be discussed by the panel, and others, include comparisons with other representations of Theories of Change and other approaches to the exploration of alternative futures, described variously as scenario planning, futures or foresight work. Speakers: Rick Davies, Lara Mani Tom Hobson An overview of the app can be found here: https://mscinnovations.wordpress.com/ The app website is here: https://parevo.org/